Interaction between non-homologous portuguese isolates of Albugo candida and Brassica oleracea - Jorge, Lurdes (2000)
The interaction of five non-homologous portuguese isolates of A. candida (four isolated from B. rapa – Ac506, Ac508, Ac509 and Ac510, and one from Raphanus sativus) in forty B. oleracea accessions from different geographic origins was evaluated at the cotyledonar stage. Some accessions presented susceptibility to the non-homologous isolates of B. rapa, mainly head cabbage ‘Large Blood Red’ and savoy cabbage ‘Brusselse Winter’. These accessions exhibited mean levels of infection higher than 20 and 46.7% respectively, independently of the B. rapa isolate tested. The isolates Ac508 and Ac510 revealed higher pathogenicity in the B. oleracea accessions tested than isolates Ac506 and Ac509. The isolate from R. sativus was the less pathogenic for the B. oleracea accessions tested. The kale ‘Verza San Giovanni’ was the accession that exhibits higher susceptibility to this isolate with 20.7% of infected plants. Non-homologous isolates of B. rapa and R. sativus were able to colonize some B. oleracea host accessions, which means that it is important to study the interaction and the variability between different Brassica accessions and isolates, and to review the concept of "races" of A. candida to formae speciales.